Compost and biogas residues as basic materials for potting substrates - T.C.V. Do; H.W. Scherer (Plant, Soil and Environment, 2012)
Recent concerns over the environmental impact of peat harvesting have led to restrictions on the production of peat based potting substrates. Therefore the objective of our study was to evaluate the use of compost and biogas residues without and each with 20% additives (Perlite, Styromull, Hygromull, Lecaton, Peat, Cocofiber) as a substitute for peat. Ryegrass (Lolium perenne L.), chosen as an experimental plant, was cut four times. The results reveal that compost and biogas residues are suitable potting substrates. The incorporation of additives mixed into the basic materials partly resulted in higher yield and nutrient uptake. However, the difference among additives was mainly insignificant. Incorporation of Hygromull, especially into biogas residues favored plant growth and increased the uptake of nutrients, which is attributed to the fact that Hygromull stores nutrients and delivers them even later in the growing season. Furthermore Hygromull reduces the salt concentration of the medium, resulting in favored plant growth of younger plants.